Effects of major histocompatibility genes and antigen delivery on induction of protective mucosal immunity to E. acervulina following immunization with a recombinant merozoite antigen. - Lillehoj, H S (1990)
Intramuscular immunization with the recombinant p250 surface antigen of Eimeria acervulina merozoite (rEAMZp250) or oral inoculation with live recombinant Escherichia coli expressing the rEAMZp250 protein resulted in antigen-specific T-cell and humoral responses and conferred a significant reduction in mucosal parasitism compared to immunization with the negative control antigen preparation. Among the major histocompatibility complex (MHC) (B)-congenic chickens receiving intramuscular immunization, strain .6-2 (B2-B2) showed significant (P less than 0.05) protection to live E. acervulina challenge compared to the other strains examined. In contrast, strains .C-12(B12B12) and .P-13 (B13B13) showed significant protection among the groups given live recombinant E. coli. In general, strains showing enhanced T-cell responses to the rEAMZp250 protein were better protected compared to those showing minimal or no T-cell responses. Thus the results suggest that the B haplotypes of the host and the mode of antigen presentation influence the outcome of protection following an immunization of chickens with recombinant coccidial antigen.